Training and health assistance for the elderly at the Griya Asih Home Care-Lawang, Malang - Wardojo, Sri Sunaringsih Ika; Rosadi, Rakhmad (Journal of Community Service and Empowerment, 2021)
The arrangement of systems and facilities of the home care according to the needs of the elderly is still one of the obstacles at the Griya Asih home care Lawang-Malang, so that the management of the home care needs assistance activities. This activity aimed to increase the active participation of the target community (caregivers at elderly home care) in overcoming health problems that arise in elderly home care. The implementation methods were: (1) Training and mentoring on the rehabilitation of the elderly and (2) Training programs and health assistance for the elderly. Service activities have been carried out well according to the target, which is indicated by an increase in knowledge of 75%. In addition, the management of the elderly home care also provides positive support which is indicated by their involvement in the implementation of activities.